Implantes cortos. Reporte de treinta implantes. Parte I: oseointegración (2011)
ABSTRACT: The purpose of this clinical report is to present the collected results with an implant system that modifies the classical protocol regarding drilling speed, use of irrigation, native bone collecting and prosthetic options including crown integrated to the abutment, extraoral cementing of the crown and universal position of abutment screw. Regarding implant design, it´s important to highlight the use of short implants, with reduced platform, lateral wings instead of screw threads, abutment connection by means of friction and modified implant surface. Methods: 30 Bicon® implants, all six-mm of length, were placed in order to perform single tooth restorations in 22 patients. The surgical protocol was performed according to indications of the manufacturer in two surgical stages. The implants were uncovered and all metal-ceramic crowns were cemented. Results: the percentage of osseointegration success was 100% at the time of uncovering, without pain or mobility during function, no signs of infection and healthy appearance of peri-implant tissues. There were no radiographic changes at the x-ray evaluation. Conclusion: considering the limitations of this study, it can be concluded that with the modified surgical protocol and the structural design of the Bicon® Implant (Bicon™ Dental Implants, Boston, MA) a 100% osseointegration success was achieved on 30 implants with modified surface and reduced platform, placed in different areas of the oral cavity for single-tooth restoration.